Tip-over prevention system based on motion prediction for teleoperated excavator. (2nd December 2021) - Shigematsu, Kosuke; Tsubouchi, Takashi; Sarata, Shigeru
Abstract : Teleoperated hydraulic excavators used in the initial response to disasters have a high risk of tipping over due to communication delays, lack of information and dangerous work sites. We proposed tip-over prediction system based on motion prediction for a teleoperated excavator. The system predicts a future motion of excavator when an operation input is given. This allows the determination of a risk of tip-over by an operation input before an excavator moves. When the risk is detected, the operation input to the actuator is modified to keep the excavator from tip over. Future motion of excavator is predicted by computing in real time the movement of a teleoperated excavator based on a simple motion model of actuators. The proposed method successfully demonstrates tip-over prevention at a steep slope via simulation experiments. GRAPHICAL ABSTRACT: UF0001